Contextual Factors and Programme Theories Associated with Implementing Blue Prescription Programmes: A Systematic Realist Review. (5th April 2023) - Alejandre, Julius Cesar; Chastin, Sebastien; Irvine, Katherine N.; Georgiou, Michail; Khanna, Preeti; Tieges, Zoë; Smith, Niamh; Chong, Yong-Yee; Onagan, Frances Claire; Price, Lesley; Pfleger, Sharon; Helliwell, Rachel; et al.
Abstract : Nature-based social prescribing such as "blue prescription" promotes public health and health improvement of individuals with long-term health conditions. However, there is limited evidence explaining the relationship of contexts, mechanisms, and outcomes of implementing blue prescription programmes (BPPs) in health and social care settings that could inform policy and practice. We conducted a systematic realist review by searching PubMed, Web of Science, PsycInfo, Scopus, MEDLINE, and CINAHL for articles published in English between January 2000 and June 2022 about health and social care professionals providing referral to or prescription of blue space activities (e.g., swimming, fishing, surfing, etc.) with health-related outcomes. Components and descriptions of BPP implementation were extracted and used to develop themes of contextual factors used to develop programme theories and a logic model demonstrating the mechanisms of BPP implementation. Sixteen studies with adequate to strong quality were included from 8, 619 records. After participating in BPPs referred to or prescribed by health and social care professionals, service users had improvements in their physical, cognitive (mental), social health, and proenvironmental knowledge. Service user-related contextual factors were referral information, free equipment, transportation, social support, blue space environments, and skills of service providers. Programme-related contextual factors were communication, multistakeholder collaboration, financing, and adequate service providers. Programme theories on service user enrolment, engagement, adherence, communication protocols, and programme sustainability explain the mechanisms of BPP implementation. BPPs could promote health and wellbeing if contextual factors and programme theories associated with service users' characteristics and programme delivery are considered in the design, delivery, and evaluation of BPPs. Our study was registered with PROSPERO (CRD42020170660 ).